Proposal to optimize the flow of preparation and delivery of vehicles to dealers based on the Lean methodology - Mercado, Angel (2019)
Currently, there is a monthly breach with its vehicle delivery policy. This policy refers to said company, it refers to a minimum of 92% of units towards the points of sale. However, in the last quarter of 2017 and the semester of 2018, it has only been met from 82% to 90%. These are 5% -10% that have not come to meet in each month, but also directly to the profitability of the company. On the one hand, storage costs are increased by each car that does not arrive or dissatisfaction is generated by the customer, this is the problem of 3 main causes, which is the installation time of radios, installation of alarms and more vehicles that are not served in the damage assessment area. As a root cause, we have the first, since, on the one hand, a bottleneck is generated by the lack of car attention and, on the other hand, represents 20% of the monthly sales of the case study, For what needs to be done to reduce this bottleneck and increase the capacity of the vehicles in this area, the damage is detailed, two lines of evaluation are carried out. This type of triage, we ensure a standardized work, since there was a group of vehicles waiting with different types of damage in the same operating line. Also, the delivery of vehicles on time is improved to 95% and the times of the areas of installation of radios, installation of alarms and damage assessment are reduced by 42.85%, 51.42% and 50% respectively.